The Genome of RNA Tumor Viruses Contains Polyadenylic Acid Sequences - Green, Maurice (1972)
The 70S genome of two RNA tumor viruses, murine sarcoma virus and avian myeloblastosis virus, binds to Millipore filters in buffer with high salt concentration and to glass fiber filters containing poly(U). These observations suggest that 70S RNA contains adenylic acid-rich sequences. When digested by pancreatic RNase, 70S RNA of murine sarcoma virus yielded poly(A) sequences that contain 91% adenylic acid. These poly(A) sequences sedimented as a relatively homogenous peak in sucrose gradients with a sedimentation coefficient of 4-5 S, but had a mobility during polyacrylamide gel electrophoresis that corresponds to molecules that sediment at 6-7 S. If we estimate a molecular weight for each sequence of 30,000-60,000 (100-200 nucleotides) and a molecular weight for viral 70S RNA of 3-12 million, each viral genome could contain 1-8 poly(A) sequences. Possible functions of poly(A) in the infecting viral RNA may include a role in the initiation of viral DNA or RNA synthesis, in protein maturation, or in the assembly of the viral genome.